The Characterological Imperative: On Heckman, Humphries, and Kautz's The Myth of Achievement Tests: The GED and the Role of Character in American Life - Sampson, Robert J. (Journal of Economic Literature, 2016)
James J. Heckman, John Eric Humphries, and Tim Kautz make a powerful case for noncognitive skills—or what they conceptualize as character—as an explanation of educational achievement and other important outcomes in life. They do so while exposing the myth of the GED, arguing that the GED harms its intended beneficiaries by failing to instill the character skills that predict adult success. Childhood interventions to build personal character, especially self-control, are emphasized. The Myth of Achievement Tests is a major contribution, but I integrate relevant research on crime and social control across the life course that motivates a more dynamic conceptualization of character. I also review evidence on the environment as a source of both cognitive and noncognitive skills, including exposure to concentrated deprivation, violence, and lead toxicity. Moreover, I review evidence suggesting that social reactions to character shape life chances in ways not reducible to individual propensities, such as changes in criminal-justice policy that created large cohort differentials in incarceration for the same underlying behaviors. Social context and the character of American society itself are thus central to fostering individual character—not just skills but the desire to conform. It follows that self-control and social control need to be better unified theoretically and in designing interventions. (JEL I21, I26, I28, J24, R23, Z13)